The Study Of Bulughul Maram In The Perspective Of Persis Scholars: (The Influence of Thought and Criticism towards The Work Of Ibnu Hajar Al-Asqalani As Obligatory Study Among PERSIS) - Rafid Abbas (International Journal of Advanced Science and Technology, 2020)
The most monumental work of Ibn Hajar al-’Asqalani is the Bulughul Maram; the book is used in many schools of thought, while Ibn Hajar has Shafi’i school. Besides, the book is also used by Muslims around the world, majelis taklim (Quran study congregations), Islamic University, and scholars of Persatuan Islam (Islamic Union/Persis). Since the beginning of the establishment of the organization, Bulughul Maram is crucial among book Persis scholars. A. Hasan, one of Persis scholars who develop the organization, is an initiator for the book to be used for Muslims in general and compulsory study of Persis members and its Islamic Boarding Schools in particular. Among the features of the book contains arguments of Islamic sharia law without any commentary and fatwa from the ulama ’. The hadiths are presented concisely even the contents of the hadith have a common with other narrations outside the book. When many hadiths are not commented, the hadith is shahih (valid). As a result, the book is easy to learn by beginners, experts, and students of Persis Islamic Boarding School all over Indonesia. Nevertheless, the work of Ibn Hajar has weaknesses, such as if the hadiths are problematic due to the existence of commentary, the other narratives will have a different final evaluation, which is not explained by Ibn Hajar. From this point, Persis cadres give criticism toward the weaknesses, so the book was studied and criticized before putting into practice among the cadres.